2022
DOI: 10.1590/1983-1447.2022.20210170.en
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with dating violence among public school adolescents

Abstract: Objective Identify the prevalence and factors associated with dating violence among school adolescents. Method Quantitative, descriptive, cross-sectional study, conducted in a state public school in Recife, Pernambuco, in August 2018, with 270 adolescents, aged between 12 and 19 years, from middle and high school. A form was applied with questions about the characterization of the adolescents, the experience of dating relationships, and the Conflict in Adolescent Dating Relationships Inventory. Pearson’s ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
1
2
0
1
Order By: Relevance
“…Families influence the formation of behavior towards violence (Rodrigues et al, 2022). In our case, it is observed how the family plays a role in defending the possible victim in line with what was observed by Reina-Barreto (2021), where the family is the main support of the victim.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Families influence the formation of behavior towards violence (Rodrigues et al, 2022). In our case, it is observed how the family plays a role in defending the possible victim in line with what was observed by Reina-Barreto (2021), where the family is the main support of the victim.…”
Section: Discussionsupporting
confidence: 82%
“…Violence is observed in a bidirectional way, something that shows the importance of focusing on men as victims of this violence in relationships, as highlighted by Sánchez-Villegas et al (2023) and Pérez-Sánchez et al (2020). Although, as in the research by Rodrigues et al (2022) and Reina-Barreto (2021), a higher prevalence is observed among women. As Rey-Ancona and Martínez-Gómez (2021) point out, men suffer dating violence, but the effects of violence are more negative in women, from the deterioration of physical and psychological health to social, family and social networks.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…A violência no namoro entre adolescentes é um campo de estudo relativamente recente no Brasil, passando a figurar no cenário científico nacional na segunda década dos anos 2000 (Minayo et al, 2011), realidade diferente em países como Estados Unidos (Basile et al, 2020) e Canadá (Exner-Cortens et al, 2022). Além das altas taxas de perpetração/vitimização (Rey-Anacona et al, 2021;Borges et al, 2020;Veríssimo et al, 2022), consideram-se os desdobramentos que podem impactar a saúde física, mental e social do adolescente ao longo do ciclo vital (Ferreira et al, 2019;Centers for Disease Control and Prevention [CDC], 2021).…”
Section: Introductionunclassified